Staying Despite Unethical Leadership: Evidence from Indonesian State-Owned Enterprises - Agustian Budi Prasetya; Nyiayu Olivia Miranda Bakrie; Cellila Aditama (Penerbit Goodwood, 2026)
Purpose: This study examines the effect of UL on employees’ Intention to Stay (ITS) in Indonesian SOEs, investigating the mediating role of PGS and the moderating role of RC. Research Methodology: Data were collected through an online survey of SOE employees aged 18–60 years with a minimum tenure of two years. Using non-probability sampling, 156 valid responses were analyzed using PLS-SEM. Results: PGS had a strong positive effect on ITS (? = 0.638, p < 0.001), emerging as the primary driver of employee retention intentions. In contrast, UL did not significantly influence PGS (? = 0.094, p > 0.05), and PGS did not mediate the relationship between UL and ITS. Likewise, the moderating effect of RC on the UL–PGS relationship was non-significant (? = 0.004, p > 0.05). Conclusions: Based on the empirical results, this study concludes that ITS in Indonesian SOEs is driven primarily by PGS rather than direct exposure to UL. Limitations: The event-based measurement of UL may not capture cumulative exposure effects, and the focus on Indonesian SOEs may limit generalizability to other organizational contexts. Contributions: Strengthening the PGS is a more effective retention strategy than focusing solely on reducing the UL. This study highlights the importance of development-oriented work design and accountability structures in sustaining ITS within highly structured organizations, such as Indonesian SOEs.